Classical and Physical Security of Symmetric Key Cryptographic Algorithms - Baksi, Anubhab; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book consolidates several key aspects from the state-of-the-art research in symmetric key cryptography, which is among the cornerstones of digital security. It presents the content in an informative yet beginner-friendly, accompanied with toy examples and comprehensible graphics. In particular, it highlights the recent developments in tool-assisted analysis of ciphers. Furthermore, promising device-dependent attacks, such as fault attack and side channel attacks on symmetric key ciphers, are discussed in detail. One salient feature of this book is to present a detailed analysis of various fault countermeasures. The coverage of our book is quite diverse it ranges from prerequisite information, latest research contribution as well as future research directions. It caters to students and researchers working in the field of cryptography. .
Introduction -- Fundamentals of Symmetric Key Cryptography -- Fault Attack -- Side Channel Attack -- New Insights on Differential and Linear Bounds using Mixed Integer Linear Programming -- Machine Learning Assisted Differential Distinguishers for Lightweight Ci-phers -- Differential Paradox: How an SBox Plays against Differential Fault Analysis -- DeFault: Cipher Level Resistance against Differential Fault Attack -- To Infect or Not to Infect: A Critical Analysis of Infective Countermeasures in Fault Attacks -- A Novel Duplication Based Countermeasure To Statistical Ineffective Fault Analysis -- Concluding Remarks.
Keywords: Electronic circuits; Cryptography; Data encryption (Computer science).; Data protection; Electronic Circuits and Systems; Cryptology; Data and Information Security